Development and validation of a scale to measure the care needs of Crohn's disease patients: a mixed-methods study - Danlei Chen; Qing Liu; Zhihui Yu; Ting Pan; Ailing Zhang; Yan Chen; Fang Kong; ChengLiang Ding (BMC, 2024)
Abstract Background Crohn's disease (CD) patients require varying levels of supportive care. In order to facilitate caregivers and nurses in precisely evaluating the caregiving requirements of these patients, we developed the CD-specific Care Needs Scale (CD-CNS). Methods This study employed a mixed-methods approach, integrating qualitative and quantitative methodologies. The initial items of the scale were developed through qualitative interviews, Delphi expert consultation, and literature review, while the final items were refined through clinical testing. Qualitative interviews were conducted based on the supportive care needs framework and Maslow's hierarchy of needs, and scale items were constructed through a literature search and qualitative interviews. The initial version of the scale with 45 items was obtained after the items were verified and modified by expert consultation. A total of 250 CD patients admitted to the gastroenterology department of a hospital in China were selected for verification of the initial version of the scale. A self-designed general questionnaire was used to obtain patients' medical history and sociodemographic data, and the Chinese version of the Inflammatory Bowel Disease Questionnaire (IBDQ) was used as the criterion. Exploratory factor analysis (EFA) was performed on the CD-CNS to evaluate the dimensions, factor structure, reliability, criterion validity, and construct validity. Results EFA identified 5 dimensions and retained 27 items with strong internal consistency reliability (α = 0.940). The Cronbach's α coefficients for each dimension ranged from 0.824 to 0.921. Criterion validity was assessed using Spearman's coefficient, which demonstrated a significant correlation with the IBDQ (P < 0.050). The test-retest reliability for each dimension after two weeks ranged from 0.655 to 0.895. Conclusions We developed and validated a new scale that can be used to assess the care needs of CD patients. This new tool can guide the specific supportive care of CD patients. Trial registration This study was reviewed and approved by the Ethics Committee of the Second Hospital of Nanjing (2021-LS-ky-022). The study was duly registered and approved online through the Trial Center of the Second Hospital of Nanjing in 2021. Confidentiality was ensured by anonymizing all the data. The entire study process was conducted under the supervision of the Ethics Committee of Nanjing Second Hospital. Informed consent was obtained from the patients, and each patient volunteered and agreed to participate.